Opportunities and Challenges in the Implementation of Plurality - Majority (District) Electoral System for Strengthening the Indonesian Presidential System - Aris, Mohammad Syaiful (Yuridika, 2022)
Presidential government system has its own disadvantages, one of them is the possibility a minority president presence in this system, namely a president who is not supported by a parliamentary majority, even though the President has a strong mandate from public, but with a minority position, the government's agenda which carried out by the president could be hampered by parliament or the legislature, therefore it is needed a coalition government. The combination of a presidential system with a multi-party system is difficult to implement because whoever the president is elected will be encountered with a certain condition that it is impossible to support him in parliament without forming a coalition. In order to respond the problem in strengthening the presidential system in Indonesia, the author offers a majority general election system or district system (first Past the Post) as an effort to create an effective and responsible government. This is a legal study which used two approaches, namely statutory approach and conceptual approach. Based on the results of study, it can be concluded that the majority system was more appropriate for creating an effective and responsible government because it could encourage the simplification of political parties and the responsibilities of people's representatives to the voters in each district.